AGENCY CONFLICTS IN AGRICULTURAL COOPERATIVES AND THEIR IMPLICATIONS FOR THE PRESIDENT’S SUCCESSION PROCESS - Rech, Luisa Rhoden; Binotto, Erlaine; Morais, Manoela; Dias, Álvaro Freitas Faustino; Arakaki, Katia Katsumi (Seven Editora, 2024)
Succession involves the need to replace one manager with another in the most important position in an organization. A transfer of power threatens organizational identity and harms its activities, but if well planned it represents a strategic opportunity for growth and renewal. Formal succession planning in non-profit organizations becomes a vital aspect of their survival. The objective of this article is to relate the main agency conflicts, proposed by Cook (1995), with the succession of the president or CEO in agricultural cooperatives. The presence of these conflicts in seven agricultural cooperatives in Mato Grosso do Sul was analyzed, with regard to the discussions on the succession of the president. Only the current presidents of the cooperatives were interviewed, seeking evidence of the participation of the cooperative members in decisions about succession, the way the president deals with the interests of the principals and the planning of the cooperative’s management in the long term. Aspects involving principal (cooperative members) and agent (president) in all the conflicts proposed by Cook (1995) were identified, hitchhiking, horizon, portfolio, control and costs of influence. In this sense, it was identified a lack of dialogue between principal and agent, absence of planning and discussions regarding the succession of the president, the importance of remuneration as retribution for the work performed by the agent, conflict of interest, lack of understanding of the principals when it comes to the interests of the cooperative. They should seek good performance both upstream (on the farm) and downstream (in the cooperative), but they end up abdicating the interests of the cooperative to the detriment of their own interests. DOI: https://doi.org/10.56238/sevened2024.037-110